Fib-4 index predicts prognosis after achievement of sustained virologic response following direct-acting antiviral treatment in patients with hepatitis C virus infection. Issue 2 (29th November 2022) - Ideno, Naomi; Nozaki, Akito; Chuma, Makoto; Ogushi, Katsuaki; Hara, Koji; Moriya, Satoshi; Fukuda, Hiroyuki; Numata, Kazushi; Maeda, Shin
Abstract : Objective(s): Toinvestigate liver carcinogenesis and other causes of death by collecting clinical data, including the Fib-4 index, from patients with successfully eradicated hepatitis C virus (HCV) by direct-acting antivirals (DAA) treatment. Methods: Patients ( n  = 690), who achieved a sustained virologic response (SVR) between 2014 and 2021, were identified and followed up for approximately 6.8 years; 71 incident hepatocellular carcinoma (HCC) cases were identified. The Fib-4 index was calculated at DAA-treatment initiation and HCV eradication, and its relationship with carcinogenesis and prognosis was analyzed. Results: The Fib-4 index was initially calculated and divided into three groups: Fib-4<1.45, 1.45 ≤ Fib-4<3.25, and 3.25 ≤ Fib-4 to develop HCC over time. On analysis, no carcinogenic cases were observed at Fib-4<1.45. In patients with a Fib-4 index ≥3.25, the initial HCC carcinogenic rate was higher than that in patients with Fib-4=1.45–3.25, and a significant difference was obtained between the two groups [ P  = 0.0057 (<1.45 vs. >3.25); P  = 0.0004 (<1.45–3.25 vs. >3.25)]. Regarding all 18 death and Fib-4 at treatment initiation, a significant difference was observed after stratification into two groups [Fib-4 < 3.25 and 3.25 ≤ Fib-4; P  = 0.0136 (<3.25 vs. ≥3.25)]. Significant differences were obtained in another analysis of 13 deaths, not due to HCC. Conclusions: The high Fib-4 index calculated at baseline and SVR12 significantly correlated not only with liver carcinogenesis but also with all mortality rates, including those due to causes other than liver cancer. Our findings suggest that improving liver fibrosis by eradicating HCV improves prognosis related to all etiologies.